Inquiry-Based Learning Improving Critical Thinking Ability in View of Elementary School Students Learning Motivation - Alawiah, Tuti; Maksum, Arifin; Madani, Faisal (Elementary Teacher Education Program, Majalengka University, 2024)
This research was conducted because there is a problem of low critical thinking among students in learning Social Studies in elementary schools. Improving critical thinking skills in students, requires an appropriate learning model and interesting learning media, namely by using the Inquiry-Based Learning model with the help of animated videos. The purpose of this study was to determine the difference in critical thinking of students given the Inquiry-Based Learning model and the Lecture model. This study used the 2x2 Quasi Experiment method with a sample of 56 students from the experimental group and the control group. The results of this study showed that: (1) the ability to think critically between students who learn with the Inquiry-Based Learning model higher motivation compared to students who learn with the Lecture model (2) there is an interaction between the learning model on the critical thinking ability of students (3) the critical thinking ability of students who are given the treatment of Inquiry-Based Learning learning model is higher than the Lecture model with high motivation (4) the critical thinking ability of students who are given the treatment of Inquiry-Based Learning model is higher than the Lecture model with low motivation.